2015
DOI: 10.1007/s00604-015-1541-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorescent carbon dots via microwave carbonization of citric acid in presence of tetraoctylammonium ion, and their application to cellular bioimaging

Abstract: A jelly-like form of carbon dots (C-dots) was prepared by microwave-assisted synthesis from citric acid in the presence of tetraoctylammonium bromide. The effect of the concentration of tetraoctylammonium bromide was examined. The synthesized carbon dots were characterized by UV-vis, XRD, FTIR, fluorescence and HR-TEM. Fluorescence extends from 350 to 600 nm, and the corresponding excitation wavelengths range from 300 to 460 nm. Quantum yields are at around 0.11. A cytotoxicity study showed carbon dots to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 36 publications
(35 reference statements)
2
47
0
6
Order By: Relevance
“…This is consistent with the FTIR and XPS data shown in Section . These surface‐functionalized SF‐CQDs also exhibit good colloidal stability in water and this good hydrophilicity is a favorable property to allow for further modification and applications in the biomedical field including drug delivery and diagnostics …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the FTIR and XPS data shown in Section . These surface‐functionalized SF‐CQDs also exhibit good colloidal stability in water and this good hydrophilicity is a favorable property to allow for further modification and applications in the biomedical field including drug delivery and diagnostics …”
Section: Resultsmentioning
confidence: 99%
“…Later, Bhaisare et al synthesized jellylike CDs with CA and tetraoctylammonium bromide (TOAB) using microwave assisted heating (at maximum 500 watt). [56] Four unique CA to TOAB ratios (5g CA: 2/4/6/8 mL of 0.1 M TOAB) were applied in the synthesis, with the obtained CDs named as C-dots I, II, III, and IV, respectively. The authors also reported that an optimum reaction time of 2–3 min produced the desired yellowish CDs.…”
Section: Citrate-based Carbon Dots (Cds)mentioning
confidence: 99%
“…To demonstrate the in vitro cell labeling capability of CDs, Bhaisare et al developed a type of biocompatible CDs with excitation-dependent fluorescence from CA and tetraoctylammonium bromide, and applied these CDs to label HeLa cells under blue fluorescence. [56] Zholobak also applied CDs synthesized from CA and urea for live/fixed diploid epithelial swine testicular cell line (ST-cells) staining. [74] Furthermore, in vivo bioimaging was also conducted with citrate-based CDs.…”
Section: Citrate-based Carbon Dots (Cds)mentioning
confidence: 99%
“…The XRD spectrum of RCD is narrower than that of PCD, implying less amorphous structural feature of RCD compared to PCD. The broad peak is due to the various functional groups existing in CD structure and its small size . FTIR spectrum exhibited sharp and intense peaks such as CH stretching (2976 cm −1 ), CO stretching (1045 cm −1 ), and CH out‐of‐plane bending (879 cm −1 ) in FTIR spectrum.…”
Section: Resultsmentioning
confidence: 99%